2022
DOI: 10.1186/s12885-022-09808-6
|View full text |Cite
|
Sign up to set email alerts
|

A role for ceruloplasmin in the control of human glioblastoma cell responses to radiation

Abstract: Background Glioblastoma (GB) is the most common and most aggressive malignant brain tumor. In understanding its resistance to conventional treatments, iron metabolism and related pathways may represent a novel avenue. As for many cancer cells, GB cell growth is dependent on iron, which is tightly involved in red-ox reactions related to radiotherapy effectiveness. From new observations indicating an impact of RX radiations on the expression of ceruloplasmin (CP), an important regulator of iron m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…CP influences oncogenesis-associated pathways, including the HIF-1 signaling pathway [50]. It is also responsive to variations in oxygen and iron concentrations and is upregulated during hypoxia [51][52][53]. Understanding the role of CP assumes particular relevance in the context of iron regulation and the radioresistant hypoxic environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CP influences oncogenesis-associated pathways, including the HIF-1 signaling pathway [50]. It is also responsive to variations in oxygen and iron concentrations and is upregulated during hypoxia [51][52][53]. Understanding the role of CP assumes particular relevance in the context of iron regulation and the radioresistant hypoxic environment.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the role of CP assumes particular relevance in the context of iron regulation and the radioresistant hypoxic environment. In a study conducted by Roy et al [51], the radiation responses of two human GBM cell lines were analyzed. They found that CP showed significant downregulation at the transcript and protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…Iron oxidation is another important function of CP. CP can transfer electrons to oxygen via regulating copper, which oxidizes Fe 2+ to Fe 3+ and enters the cell after binding to transferrin, thus providing sufficient iron for cell proliferation ( Forciniti et al, 2020 ; Roy et al, 2022 ). Depletion of CP caused the accumulation of ferrous iron (Fe 2+ ) in cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Some recent studies stated that the abnormal CP expression occurring in the brain could be attributed to a few neurological diseases ( Klomp and Gitlin, 1996 ; Qian and Ke, 2019 ; Villadsen et al, 2023 ). At present, the existing literature studies have reported that in the iron-deficient and iron-saturated cells, CP, regardless of concentration, promotes the uptake of transferrin-bound iron and ferric citrate by glioma cells ( Attieh et al, 1999 ; Roy et al, 2022 ). Moreover, high expression of CP in tumor cells, such as lung cancer ( Chang et al, 2022 ), liver cancer ( Shang et al, 2020 ), melanoma ( Liu et al, 2022a ), and breast cancer ( Chen et al, 2021 ), can inhibit ferroptosis, thus reduces tumor cell death and promotes tumor progression.…”
Section: Introductionmentioning
confidence: 99%
“…GO analyses of biological processes and pathways downregulated in NSC populations vs. GSCs revealed that tumorigenic stem cells showed an increased expression of genes driving the cell cycle (including MYC and E2F TFs); oxidative phosphorylation-dependent ATP biosynthesis, typically detected in cancer vs. somatic stem cells 137 ; synthesis of selenoproteins, which play a key role in oxidative stress regulation in glioblastoma (e.g. GPX1 and GPX4 [138][139][140][141][142][143] ); and L13a-mediated silencing of ceruloplasmin, an important regulator of iron metabolism which positively correlates with the efficacy of radiotherapy on GBM cells 144 (Fig. 6C-E; Suppl.…”
Section: Hipsc-nscs Are Transcriptionally Divergent From Glioblastoma...mentioning
confidence: 99%